Juridical Overview of the Parole Process For 1/2 (Half) Period of Imprisonment in the Fulfillment of the Rights of Students - Sufmi Dasco Ahmad (Budapest International Research and Critics University, 2022)
One of the rights of children who are undergoing a criminal period is to obtain parole 1/2 (half) of the criminal period. The implementation process at the Bandung Class II Special Child Development Institute is still relatively new (in 2017). Therefore, various problems are encountered in its implementation. The purpose of this study is to find out (1) what are the obstacles in the process of implementing parole 1/2 (half) of the criminal period for students in LPKA Class II Bandung. (2) To find out how to overcome the obstacles that arise in the implementation of parole 1/2 (half) of the criminal period in LPKA Class II Bandung. The method used in this research is descriptive analytical with a normative juridical approach. Data collection techniques through literature review are complemented by field studies through interviews with certain parties. The data analysis was carried out qualitatively and the results of the study concluded that the obstacles faced in the implementation of the granting of parole related to various things (1) the students had never been visited by their families, as a result the background of the child was unknown, and the students did not want to take part in the release program. In addition, the community does not want to accept children back into their midst because they are worried about the repetition of crimes, also the process of applying for parole is rather complicated and takes a long time because it involves various parties. (2) To overcome the obstacles that arise, a